2014
DOI: 10.4103/2303-9027.127122
|View full text |Cite
|
Sign up to set email alerts
|

How good is fine needle aspiration? What results should you expect?

Abstract: Tissue acquisition plays a key role before treatment decision in most of oncological pathologies but also in several benign diseases. By offering tissue sampling, endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) has become an essential tool in the diagnostic processes. One of the reasons for the success of the technique is related to its excellent diagnostic performance. The diagnostic accuracy of EUS-FNA is above 80% for most of the usual indications. These performances are however dependent on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…EUS‐FNAC has been shown to have a high level of diagnostic accuracy in the assessment of solid pancreatic lesions. In combination with EUS findings and cyst fluid biochemistry, it is also of significant diagnostic utility in the assessment of pancreatic cystic lesions …”
Section: Introductionmentioning
confidence: 99%
“…EUS‐FNAC has been shown to have a high level of diagnostic accuracy in the assessment of solid pancreatic lesions. In combination with EUS findings and cyst fluid biochemistry, it is also of significant diagnostic utility in the assessment of pancreatic cystic lesions …”
Section: Introductionmentioning
confidence: 99%
“…Standard aspiration needles were originally designed to obtain cellular material for cytopathological examinations [110,484,485]. The cytological yield and diagnostic accuracy, in studies using predominantly 22 G aspiration needles, are reported to be high for solid pancreatic lesions and metastatic lymph nodes, satisfactory for biliary mass lesions, but only moderate for gastrointestinal SETs and PCLs ( • " Table 3) [104,110,486,487]. Currently, the 22 G aspiration needle is most widely used, with increased utilization of 25 G aspiration needles particularly for sampling and cytopathological evaluation of pancreatic lesions and lymph nodes [149,488,489].…”
Section: Eus-guided Fine-needle Aspiration For Cytopathological Procementioning
confidence: 99%
“…Endoscopic ultrasound (EUS)‐guided fine‐needle aspiration (FNA) plays an essential role in making an accurate diagnosis and therapeutic plan for pancreatic solid mass with few major adverse events . However, the diagnostic yield, including sensitivity and specificity (75–92% and 82–100%, respectively), for pancreatic solid mass is limited especially considering the very low negative predictive value . To overcome this limitation, some attempts for the improvement of diagnostic outcomes in EUS‐guided tissue acquisition were conducted; these include the use of fanning technique, the use or elimination of suction, and the use or elimination of stylet .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the diagnostic yield, including sensitivity and specificity (75-92% and 82-100%, respectively), for pancreatic solid mass is limited especially considering the very low negative predictive value. 2,3 To overcome this limitation, some attempts for the improvement of diagnostic outcomes in EUS-guided tissue acquisition were conducted; these include the use of fanning technique, the use or elimination of suction, and the use or elimination of stylet. 4 Among these, the fanning technique was first introduced by Bang et al in 2013.…”
Section: Introductionmentioning
confidence: 99%